Infographics in Higher Education: Instructional Media for Students' Writing Proficiency - Putra, I Kadek Swartana; Ratminingsih, Ni Made; Utami, IGA Lokita Purnamika; Artini, Luh Putu; Padmadewi, Ni Nyoman; Marsakawati, Ni Putu Era (Universitas Pendidikan Ganesha, 2022)
The majority of ESL/EFL students is that writing is challenging and frustrating. Limited vocabulary and low idea gathering appears to be most difficult issues in writing process. This research was quasi-experimental, with a control group that was only used for the post-test. This research aims to analyses the effectiveness of infographics as instructional media on students' writing proficiency. Two classes totalling 64 students made up the sample, which was drawn using random cluster sampling. A writing test served as the research instrument. An independent t-test was used to assess the data. The findings indicated that the experimental group's students were more proficient writers. The experimental group did better than the control group in terms of means (85.97 > 83.48) and the t-test results (3.126 > 3.125). In comparison to the conventional instruction, it was shown that using infographics as instructional media had a substantial impact on students writing proficiency. The effect size computation yielded a result of 0.78, which was examined in the Cohen's d table. In conclusion, infographics had a significant effect on students' writing proficiency as an instructional media.